The Effect Of Noise In Ship Engine Rooms On The Safety And Health Of Ship Crews In The Engine Section - Al Atras Zatazka Eartha Firstaneo; Antonius Edy Kristiyono; Monika Retno Gunarti; Novitasari Novitasari (CV. AFDIFAL MAJU BERKAH, 2026)
The ship's engine room is an area with the highest noise level that threatens the safety and health of the crew, with exposure of 95-108 dB exceeding the NAB 85 dBA (Per.13/Men/X/2011). Objective: To analyze the effect of noise on the safety and health of engine crew. Method: Descriptive quantitative research with simple linear regression. Population and Sample: 36 engine crew from the Marine Practice program of Surabaya Maritime Polytechnic, purposive sampling. Instruments and Analysis: Sound level meter, Likert questionnaire, SPSS for regression (Y=12.490+0.441X), t-test, R². Results: Noise has a significant effect (t-count=2.346>2.034, sig=0.025<0.05), explaining 37% of the variation in risk. Conclusion: Engine room noise increases the risk of deafness, stress, and accidents; PPE and engine maintenance are required.